Sustainability Communications of Fashion Brands on social media: Central Themes and Consumer Responses - İrem AKSOY; Tugba TUGRUL (Communications of International Proceedings, 2022)
This study aims to identify central themes of sustainable messages of fashion brands posted on social media and investigate consumer responses. A quantitative content analysis of 458 posts on Instagram accounts of 16 global fashion brands was conducted. Seven and nine themes were identified in social and environmental sustainability messages, respectively. Mann-Whitney U test results show that Recycling and Biodiversity were the most frequent and engaging themes among environmental sustainability messages. Diversity and Inclusion was the most frequent social sustainability theme that also received the highest consumer responses. Moreover, environmental sustainability messages attracted more consumer responses than social messages.
Keywords: Sustainability; Communication; social media; Fashion; Brands; Consumers.